The influence of infrastructure and learning materials in Physical Education classes at state schools in the City of Amazonas State in Manacapuru City (Research, Society and Development, 2020)
The Physical Education discipline is a mandatory curricular component in Brazilian Basic Education, however, for it to happen in full, it is necessary to have, in schools, adequate learning materials and physical spaces. The aim of the study was to analyze the influence of infrastructures and learning materials for Physical Education classes in state schools in the city of Manacapuru-AM. The research was carried out in fifteen state schools in the urban area of this city in Amazonas state and is characterized as descriptive, with an exploratory character. Observations and notes were made in field diary and it was found that six schools had indoor court, six others only had patio without coverage, and three of the schools had no space beyond the classroom. Regarding learning materials, in most schools they were found in insufficient quantities for the demand of students. Finally, we concluded, from the observations, that the lack of infrastructure and didactic materials directly influenced the quality and performance of Physical Education classes.